Human and rat ex vivo sweat glands for the observation of acetylcholine induced intracellular calcium signalling - Teresa Franziska Buck; Tobias Kisch; Charli Kruse; Matthias Brandenburger (PLoS ONE, 2025)
Sweating is imperative for thermoregulatory function in humans. However, many individuals find it undesirable due to its associated malodorous nature. Despite these concerns, aluminium salts remain among the most efficacious sweat-inhibiting agents. Nevertheless, the discovery of novel antiperspirants is challenging due to restrictions on animal testing and the limitations of existing cellular models. Sweat glands, when isolated from human subjects, have been shown to possess only minor functional limitations. Consequently, they are regarded as a leading alternative, despite their limited availability. As the primary analytical metric for isolated sweat glands is sweat output, the objective of this study was to devise experiments that enhance both analysability and availability. We consequently present a method for the reliable observation of intracellular calcium responses in isolated human sweat glands ex vivo. Furthermore, we show that availability can be improved by demonstrating that isolated human sweat glands can be cryopreserved while preserving viability, structural integrity and functionality. In order to obtain these results with limited access to human sweat glands, we set up an experimental set-up using rat sweat glands and compared them to human sweat glands. The study demonstrates that isolated sweat glands from rats and humans exhibit a remarkably similar physiological calcium response to cholinergic stimulation. This validates the use of rat sweat glands as a suitable model for the development of novel experimental procedures, thus circumventing the scarcity of human sweat gland samples. This approach significantly enhanced the analysability and availability of human sweat gland samples. The calcium imaging method applied in this study facilitates the exploration of sweat gland physiology at the cellular level, thereby enabling a more detailed understanding of sweating disorders. This, in turn, enhances the suitability of the model for use in cosmetic testing and the discovery of new antiperspirant agents, thus circumventing the need for animal testing.